Association between pan-immune inflammatory value and all-cause mortality in critically ill patients with ischemic stroke: a retrospective analysis of the MIMIC-IV database (2008–2022) - Anni Chen; Jiahui Wang; Qiaoying Huang; Zhizhou Hu; Donglan Jiang; Yunnan Hu; Liying Pan; Jianhui Chen; Xiaohong Hu (Frontiers in Neurology)
BackgroundSystemic inflammation and immune responses are key contributors to the onset and progression of ischemic stroke, influencing both tissue damage and repair. This study investigates the association between the pan-immune inflammatory value (PIV)—a composite biomarker derived from routine blood tests—and all-cause mortality (ACM) in critically ill ischemic stroke patients.MethodsWe extracted data from the MIMIC-IV (v3.0) database, identifying ischemic stroke patients using ICD-9/10 codes. PIV was calculated using the formula: (monocytes × neutrophils × platelets) ÷ lymphocytes. ACM was assessed during hospitalization and at 30-, 90-, and 365-days post-admission. Multivariable Cox proportional hazards models and restricted cubic spline (RCS) analyses were used to assess the relationship between PIV and mortality. Kaplan–Meier curves, time-dependent ROC curves, and decision curve analysis (DCA) evaluated survival differences and predictive performance. Subgroup and interaction analyses were conducted using likelihood ratio tests.ResultsA total of 1,365 critically ill ischemic stroke patients were included, with 50.48% male. Elevated PIV was significantly associated with higher mortality during hospitalization (HR: 1.98), and at 30-day (HR: 2.56), 90-day (HR: 1.97), and 365-day (HR: 1.76) follow-ups (all p < 0.01). RCS analysis revealed a J-shaped relationship between PIV and ACM. Subgroup analyses showed consistent results without significant interaction effects.ConclusionPIV is an independent predictor of short- and long-term mortality in critically ill ischemic stroke patients. These findings suggest PIV could serve as a practical and cost-effective biomarker for risk stratification and prognosis in clinical settings.